2019
DOI: 10.1038/s41467-019-11877-4
|View full text |Cite
|
Sign up to set email alerts
|

A dual role of prestimulus spontaneous neural activity in visual object recognition

Abstract: Vision relies on both specific knowledge of visual attributes, such as object categories, and general brain states, such as those reflecting arousal. We hypothesized that these phenomena independently influence recognition of forthcoming stimuli through distinct processes reflected in spontaneous neural activity. Here, we recorded magnetoencephalographic (MEG) activity in participants ( N = 24) who viewed images of objects presented at recognition threshold. Using multivariate analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 71 publications
10
69
0
Order By: Relevance
“…These results demonstrate that pre-stimulus activity modulates the degree of category tuning on the trial-by-trial basis in category-selective areas of the cortex. Previous studies have mainly focused on the overall correlation between the pre-stimulus activity and the evoked response in features including phase and oscillatory power of the event-related response 23 25 , often not definitively localized to the regions that process the stimulus class being presented 41 . The results here demonstrate that pre-stimulus activity modulates the post-stimulus activity in the regions that are selective for the stimulus being viewed.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate that pre-stimulus activity modulates the degree of category tuning on the trial-by-trial basis in category-selective areas of the cortex. Previous studies have mainly focused on the overall correlation between the pre-stimulus activity and the evoked response in features including phase and oscillatory power of the event-related response 23 25 , often not definitively localized to the regions that process the stimulus class being presented 41 . The results here demonstrate that pre-stimulus activity modulates the post-stimulus activity in the regions that are selective for the stimulus being viewed.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing appreciation of the relationship between arousal, pupil size, and cognitive performance [15][16][17][18][19]. For example, unlike spatial attention, which increases perceptual sensitivity in a local region in visual space, changes in arousal lead to pupil dilation and do not necessarily increase sensitivity [15,20,21]. If this hypothesis is correct, then task-related hemodynamic activity may contain important information about cognitive processes, which is overlooked by the vast majority of fMRI experiments.…”
Section: Introductionmentioning
confidence: 99%
“…György Buszáki (Buzsáki, 2019) suggests an alternative approach, ‘inside-out’; unlike the traditional ‘outside-in’, it places intrinsic neural activity as a key factor (inside) in modulating activity change related to external stimuli (outside) (see also Northoff et al 2010, Northoff 2014a and b). Consistent with this approach (Buzsáki, 2019), studies (He, 2013; Baria et al, 2017; Huang et al, 2017; Nieus et al, 2018; Galindo-Leon et al, 2019; Hirschmann et al, 2019; Podvalny et al, 2019) have demonstrated that poststimulus activity levels depend on the initial state, the level of prestimulus activity (Yamagishi et al, 2008; Mathewson et al, 2009; Northoff et al, 2010; Fellinger et al, 2011; Hanslmayr et al, 2013; He, 2013; Milton and Pleydell-Pearce, 2016; Benwell et al, 2017; Huang et al, 2017; Hirschmann et al, 2019). These findings demand the question: how and in what way do prestimulus activity levels shape stimulus-induced activity beyond the external stimulus?…”
Section: Introductionmentioning
confidence: 72%